If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x^2=7x+1
We move all terms to the left:
6x^2-(7x+1)=0
We get rid of parentheses
6x^2-7x-1=0
a = 6; b = -7; c = -1;
Δ = b2-4ac
Δ = -72-4·6·(-1)
Δ = 73
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-7)-\sqrt{73}}{2*6}=\frac{7-\sqrt{73}}{12} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-7)+\sqrt{73}}{2*6}=\frac{7+\sqrt{73}}{12} $
| 5=-9+6x | | 98x-7=94x+21 | | 4a=10a-6 | | 6(x+5)+20=2x+17 | | 6x—2=7x+1 | | 8x+7=42+2x | | (2x/3)+(3x/4)=1 | | 4(v+2)=4(v+1) | | 3x+9-6x=21 | | 10(8x-11)=690 | | 5(8x-3)=345 | | .a/3-2=4 | | -10+7u+17u=18u+20 | | 700/3*2=n | | 4.4+n=-4.6-2n | | 18f+10=19f | | 5(2x-2)=10x-4+2 | | -3x-(7-6x)=14x+15 | | 5(5x-19)=55 | | p/4=7/10 | | -20+18p=20+20p | | 9n+6(n+12)=12 | | 3n=42. | | (7/5)x-7=2.8 | | -5x+7+11x-13=24 | | 7(x+6)=147 | | -5x+11=-6 | | c+2=2c-5 | | s+17=16s-11s-19 | | 11-7y=39 | | 6(6x-3)=378 | | -39c=0 |